A Dual-Polarized Broadband High Gain Base Station Antenna With an Octagonal Structure - Chengbin Zhang; Yuhui Zhang; Xiwang Dai; Zehong Yan (IEEE Access, 2023)
In this paper, a dual-polarized broadband high gain base station antenna unit is proposed. The antenna unit comprises an octagonal radiation structure and a pair of orthogonal $Γ $ -shaped feeding structure, stacked patch and metal reflection structure. The octagonal radiation structure can effectively increase the radiation area, and the wide working frequency band can be realized by means of coupling and slotting. At the same time, high isolation and stable radiation pattern characteristics can be obtained. The simulation results show that the impedance bandwidth of the antenna is 47% (1.67 - 2.69 GHz) when the reflection coefficient is less than - 20 dB, and the port isolation is greater than 27 dB, a high gain of 10 ± 0.5 dBi can be obtained in the passband. Furthermore, the antenna also obtains a wide half power beam width (HPBW). The HPBW fed through a single port and two ports are around 60°. Finally, the antenna unit is applied to the $4×11$ antenna array to realize the multi-band dual polarization system.